Antibiotic therapy is associated with adverse drug events among older adults with advanced cancer: A cohort study. (May 2023) - Datta, Rupak; Han, Ling; Doyle, Margaret; Allore, Heather; Sanft, Tara; Quagliarello, Vincent; Juthani-Mehta, Manisha
Background: Older adults with advanced cancer are exposed to antibiotics but estimates of adverse drug events associated with antibiotic therapy are lacking. Aim: Evaluate the association of antibiotic therapy with adverse drug events in older adults with advanced cancer. Design: Cohort study where the exposure was the ratio of days of therapy of an oral or intravenous antibiotic per patient-day and the outcome was an adverse drug event, defined as cardiotoxicity, hepatotoxicity, nephrotoxicity, Clostridioides difficile infection, or new detection of a multidrug-resistant organism. Setting/participants: Patients aged ⩾65 years with solid tumors from a tertiary care center who received palliative chemotherapy ( n = 914). Results: Mean age was 75 ± 6.6 years, and 52% were female. Common tumors were lung (31%, n = 284) and gastrointestinal (26%, n = 234). Mean time from first course of palliative chemotherapy to index admission was 128 days. Five-hundred thirty (58%) patients were exposed to antibiotics during the index admission; of these, 27% ( n = 143) met standardized criteria for infection. Patients were commonly exposed to cephalosporins (33%, n = 298) and vancomycin (30%, n = 276). Among patients exposed to antibiotics, 35% ( n = 183/530) developed an adverse drug event. In multivariable testing, antibiotic therapy was associated with development of an adverse drug event (>0 to <1 vs 0 days of therapy/patient-day: adjusted odds ratio [aOR] = 1.9; 95% confidence interval [CI], 1.2–2.8; ⩾1 vs 0 days of therapy/patient-day: aOR = 2.1, 95% CI, 1.4–3.0). Conclusion: Antibiotic therapy was independently associated with adverse drug events in hospitalized older adults with advanced cancer. These findings may inform antibiotic decision-making among palliative care providers.